Diasporic medical tourism: a scoping review of quantitative and qualitative evidence - Aneta Mathijsen; François Pierre Mathijsen (BMC, 2020)
Abstract Background There is a growing recognition of the significance of the diasporic dimension of medical travel. Explanations of medical tourism are increasingly presented in a wider context of transnationalism, diaspora and migration. Yet diaspora and cross-border travellers rarely get through the broader narrative of medical travel. Objective Our aim in this scoping review was to extend the current knowledge on the emerging subject of diasporic travels for medical purposes. Specifically, we reviewed the existing literature on what is known about the determinants and motivational factors of diasporic medical tourism; its geographic scope and its quantitative estimation. Methods Using a scoping review methodology, we conducted the search in seven electronic databases. It resulted in 210 records retrieved. Ultimately, 28 research papers and 6 non-research papers (published between 2002 and 2019) met the following criteria: 1) focus on healthcare and health-related practices, 2) transnational perspective, 3) healthcare consumption in the country of origin (homeland) while being a resident of another country, 4) published in English. Results The findings from our review highlighted the importance of diasporic medical patients who had been researched and analysed on four continents. Even though quantitative evidence has been scarce, the data analysed in the scoping review pointed to the existence of non-negligible level of diasporic medical tourism in Northern America, and in Europe. Various motivational factors were enumerated with their frequency of occurrence: medical culture (12), time availability ("by the way of being home") (9), communication (6), dissatisfaction with the current system (6), healthcare insurance status (5), quality of healthcare (5), second opinion (3), and value for money (3). Conclusion Diasporic medical tourists constitute an attractive segment of consumers that is still not well understood and targeted. They are part of transnational communities that cultivate the links between the two nations. They simultaneously participate in bi-lateral healthcare systems via return visits which impact the health systems of sending and receiving countries in a substantial way. In the current globalised, connected and migratory context, transnationalism seems to represent an answer to many local healthcare-related barriers. Sending and receiving countries have put in place an array of programmes and policies addressed to the diasporic medical travellers.